Inverse functions - Kudžma, Ričardas Juozas (Lietuvos matematikos rinkinys, 2025)
23 years ago, R. Kudžma in the journal Alfa plius omega [7] argued that the TEV textbook [14] presents the inverse function and its graph incorrectly. The head of the textbook's author group, V. Stakėnas [15], replied that this was not incorrect, but a traditional approach. The discussion did not develop. The separation of the function f  : x  ↦ f(x), o y = f(x) and the equation y = f(x) notations proposed in this article may help resolve the seemingly irreconcilable views on the inverse function and its graph. The idea is also developed that the graph of the function f in the original coordinate system Oxy is also the graph of the inverse function in Oyx coordinate system.
Keywords: function's definition; function's notation; graph of a function; inverse function; coordinate system